Production of bacterial pigment by fermentation of serratia marcescens for dye sensitized solar cell - Chong, Li Yee (Universiti Malaysia Sarawak (UNIMAS), 2017)
A conventional ruthenium complex based dye sensitized solar cell (DSSC) is costly. The process of the ruthenium complex production and ruthenium complex based DSSC disposal are not environmental friendly. Organic pigment has been proposed as alternative photosensitizer for DSSC. Bacterial pigment has high potential due to the clean and cheaper microbial synthesis process. In this project, prodigiosin was aimed to be produced from the fermentation of S. marcescens in a bioreactor for the application of dye-sensitized solar cell. The optimum pH level for prodigiosin production identified through experiments was pH 7. By examining the impact of olive oil, peanut oil and palm oil towards fermentation of S. marcescens, the palm oil has the best performance in terms of cell growth yield and prodigiosin yield among other studied oil substrate. For 1g of palm oil substrate, 0.017g of biomass and 3.499mg of prodigiosin had been produced. This project had stand a novelty in study of impact of palm oil towards cultivation of S. marcescens and prodigiosin production. This study had also further proven that the production of prodigiosin is favourable in presence of oil substrate with high saturated fat content. The pink prodigiosin produced from cultivation of S. marcescens with presence of oil substrate had comparable performance with other bacterial pigment and is highly potential to be used in DSSC application. 336.1 mV and 0.098 mA had been generated by fabricated DSSC in this study.